2017
DOI: 10.1002/oby.21879
|View full text |Cite|
|
Sign up to set email alerts
|

Nonalcoholic Steatohepatitis is Associated with Cardiac Remodeling and Dysfunction

Abstract: Objective Preliminary data suggest that nonalcoholic fatty liver disease (NAFLD) is associated with early heart failure (HF). However, whether nonalcoholic steatophepatitis (NASH) is directly associated with echocardiographic changes in cardiac structure or function remains unknown. Methods We identified a retrospective cohort (N=65) without known heart disease, undergoing elective bariatric surgery with perioperative liver biopsy, and available recent transthoracic echocardiography (TTE). TTE measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 15 publications
7
56
0
3
Order By: Relevance
“…Petta et al [15] in a multivariate model found no significant differences in left ventricular mass or early annular diastolic tissue velocity in NAFLD patients. Our results are consistent with Simon et al [16], but given the conflicting evidence in the literature future studies are needed to further validate our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Petta et al [15] in a multivariate model found no significant differences in left ventricular mass or early annular diastolic tissue velocity in NAFLD patients. Our results are consistent with Simon et al [16], but given the conflicting evidence in the literature future studies are needed to further validate our results.…”
Section: Discussionsupporting
confidence: 93%
“…However, these studies provide conflicting reports on the relationship between NAFLD and LVDD. For example, Simon et al [16] showed that NAFLD was associated with significant Left ventricular diastolic dysfunction in liver transplantation echocardiographic abnormalities consistent with progressive LVDD; however, the study was limited by a small sample size and did not account for confounders of NASH and heart failure. Karabay et al [14] compared an NAFLD cohort to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The primary causes of mortality in NASH are cardiovascular: myocardial infarction, renal failure, and stroke. 27,28 We measured biomarkers of cardiovascular risk in Il11ra1 -/mice after 16 weeks on WDF. As compared with littermate controls, Il11ra1 -/mice on WDF had lower levels of fasting blood glucose, serum cholesterol, and triglycerides ( Figure 2L-N).…”
Section: Deletion Of Il11ra1 Protects Mice From Nashassociated Inflammentioning
confidence: 99%
“…In addition to liver-related complication, a growing body of evidence has indicated a close relationship between NAFLD and cardiovascular disease (CVD) [3][4][5]. Patients with NAFLD have a higher prevalence of CVD and are more likely to die from CVD than from liver-related death [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to liver-related complication, a growing body of evidence has indicated a close relationship between NAFLD and cardiovascular disease (CVD) [3][4][5]. Patients with NAFLD have a higher prevalence of CVD and are more likely to die from CVD than from liver-related death [4][5][6]. Among the categories of NAFLD, liver brosis is considered as the main indicator of prognosis in NAFLD and was found to be independently associated with CVD and motality in different populations [6][7][8].…”
Section: Introductionmentioning
confidence: 99%